Effects of Product Quality, Price and Brand Image onthe Purchasing Decisions of Nike Products - Nani Nani; Badriyah Badriyah; R Arynati Ratnawati (Jurnal Mantik, 2022)
Technological development supports the rapid growth of online shops. Online shopping has now become a lifestyle and habit for many people due to the convenience offered. Customers need to be more careful in making purchase decisions, including the decision to purchase NIKE preloved products at Brandedfashi online shops in Bandung. This study focused on the customer's decision to purchase preloved NIKE products. It aims to identify the impact of product quality, price, and brand perception on the decision to purchase preloved online shop products. This study used a quantitative method involving a sample of 100 respondents. The data obtained from the respondents were analyzed using Multiple Linear Regression analysis. The results show that the Fisher (F) test of the product quality, price, and brand views affect purchasing decisions of preloved NIKE products from Brandedfashi online shop. Quality is a significant aspect influencing the decision to purchase preloved products as Brandedfashi. Brand images are influenced by integrity, applied strategies, and customer perceptions. To increase customer satisfaction with preloved products, it is important to improve the advertising methods, packaging, and price compliance.